ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN: STUDI PADA PT INDOFOOD SUKSES MAKMUR TBK (INDF) / ICBP - Diana Enjelika Nainggolan; Ester Adelia Manalu; Yosua Sihaloho; Hamonangan Siallagan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the financial performance of PT Indofood Sukses Makmur Tbk (INDF) and/or PT Indofood CBP Sukses Makmur Tbk (ICBP) using a financial ratio analysis approach. Financial performance is an important aspect in assessing a company’s ability to manage resources, fulfill obligations, and create value for stakeholders. This research employs a quantitative approach with a descriptive analytical method. The data used are secondary data obtained from audited and officially published annual and consolidated financial statements for the period 2021–2024. The data analysis technique applied is financial ratio analysis, which includes liquidity, solvency, activity, and profitability ratios. The results indicate that the financial performance of PT Indofood Sukses Makmur Tbk during the research period is relatively good and stable. Liquidity ratios show the company’s ability to meet short-term obligations, solvency ratios reflect a sound capital structure with controlled financial risk, activity ratios indicate efficiency in asset utilization and inventory management, and profitability ratios demonstrate the company’s consistent ability to generate profits. Therefore, financial ratio analysis proves to be an effective tool for evaluating corporate financial performance and can serve as a basis for managerial and investment decision-making.